2023
DOI: 10.1038/s41586-023-06206-1
|View full text |Cite
|
Sign up to set email alerts
|

Martian dunes indicative of wind regime shift in line with end of ice age

Abstract: Orbital observations suggest that Mars underwent a recent ‘ice age’ (roughly 0.4–2.1 million years ago), during which a latitude-dependent ice-dust mantle (LDM)1,2 was emplaced. A subsequent decrease in obliquity amplitude resulted in the emergence of an ‘interglacial period’1,3 during which the lowermost latitude LDM ice4–6 was etched and removed, returning it to the polar cap. These observations are consistent with polar cap stratigraphy1,7, but lower- to mid-latitude in situ surface observations in support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…As mentioned above, both MarSCoDe LIBS and SWIR spectra imply the recent aqueous activity at the Zhurong landing site (e.g., ∼2.1–0.4 Ma, J. Liu et al., 2023). However, there are two interpretations regarding how the recent aqueous activity occurred: evaporation of groundwater (Y. Liu et al., 2022; J. Wang et al., 2023); saline water from thawed frost/snow (Qin et al., 2023) or water vapor cycling (Y. Y. S. Zhao et al., 2023) on the surface.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…As mentioned above, both MarSCoDe LIBS and SWIR spectra imply the recent aqueous activity at the Zhurong landing site (e.g., ∼2.1–0.4 Ma, J. Liu et al., 2023). However, there are two interpretations regarding how the recent aqueous activity occurred: evaporation of groundwater (Y. Liu et al., 2022; J. Wang et al., 2023); saline water from thawed frost/snow (Qin et al., 2023) or water vapor cycling (Y. Y. S. Zhao et al., 2023) on the surface.…”
Section: Discussionmentioning
confidence: 86%
“…The absorption features of hydrated silica or hydrated sulfates were identified in the SWIR spectra of rocks (Y. Liu et al., 2022). The dunes also exhibit spectral characteristics of hydrous minerals: hydrated sulfates, hydrated silica, trivalent iron oxide minerals, or chlorides (J. Liu et al., 2023; Qin et al., 2023); hydrated sulfates or Al‐phyllosilicates, more likely hydrated sulfates (J. Wang et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later analysis provided wind direction, terrain evolution and other information about the rover's landing area. Evidence showed that the landing area may have experienced two major climate periods with distinct directions of wind [ 3 ]. This finding is consistent with ice records from mid-to-high latitude regions on Mars.…”
Section: Climate Change On Mars Revealed In Tianwen-1 Datamentioning
confidence: 99%